Plasmatic antioxidant capacity as a possible marker of phytodrugs efficacy - Andrea Muller; I. Saavedra Saavedra; M. E. Letelier (International Journal of Phytomedicine, 2015)
A correlation between drug plasma concentration and its therapeutic effect exist. Then we postulate that determination of plasmatic antioxidant capacity could prove phytodrugs efficacy. Therefore, we determined the plasmatic ability to reduce Fe3+ and malondialdehyde concentration after orally administration of herbal extracts to rats. For this, we use hydro-alcoholic extracts of Buddleja globosa Hope and Plantago major L. previously characterized according to their polyphenol and thiol compounds contents, and their capacities to inhibit the oxidation of microsomal lipid and thiol compounds. The amounts of polyphenol and thiol compounds were three times higher in B. globosa than in P. major extracts. Moreover, EC50 of B. globosa extract in preventing oxidation of microsomal lipid and thiol compounds induced by Cu2+/ascorbate were 3 times lower. These extracts were also able to inhibit microsomal GSH-transferase activity and chelate Cu2+. The oral administration of these extracts to rats provoked an increase in the ability to reduce Fe3+ and a decrease in malondialdehyde concentration. Since the antioxidant activity of these extracts was reproduced in vivo, we believe that the efficacy of phytodrugs used in complementary therapies may be evaluated by measuring the plasma antioxidant capacity.